Reconstruction of drip-water δ18O based on calcite oxygen and clumped isotopes of speleothems from bunker cave (Germany) - Kluge, Tobias; Affek, H. P.; Marx, Thomas; Aeschbach, Werner; Riechelmann, Dana; Scholz, Denis; Riechelmann, S.; Immenhauser, A.; Richter, D. K.; Fohlmeister, Jens; Wackerbarth, Anne Katrin; Mangini, Augusto; et al. (Climate of the past, 2013)
The geochemical signature of many speleothems used for reconstruction of past continental climates is affected by kinetic isotope fractionation. This limits quantitative paleoclimate reconstruction and, in cases where the kinetic fractionation varies with time, also affects relative paleoclimate interpretations. In carbonate archive research, clumped isotope thermometry is typically used as proxy for absolute temperatures. In the case of speleothems, however, clumped isotopes provide a sensitive indicator for disequilibrium effects. The extent of kinetic fractionation co-varies in Δ47 and δ18O so that it can be used to account for disequilibrium in δ18O and to extract the past drip-water composition. Here we apply this approach to stalagmites from Bunker Cave (Germany) and calculate drip-water δ18Ow values for the Eemian, MIS3, and the Holocene, relying on independent temperature estimates and accounting for disequilibrium. Applying the co-variation method to modern calcite precipitates yields drip-water δ18Ow values in agreement with modern cave drip-water δ18Ow of −7.9 ± 0.3‰, despite large and variable disequilibrium effects in both calcite δ18Oc and Δ47. Reconstructed paleo-drip-water δ18Ow values are lower during colder periods (e.g., MIS3: −8.6 ± 0.4‰ and the early Holocene at 11 ka: −9.7 ± 0.2‰) and show higher values during warmer climatic periods (e.g., the Eemian: −7.6 ± 0.2‰ and the Holocene Climatic Optimum: −7.2 ± 0.3‰). This new approach offers a unique possibility for quantitative climate reconstruction including the assessment of past hydrological conditions while accounting for disequilibrium effects.
Gesehen am 19.11.2014
Im Titel erscheint die Zahl 18 hochgestellt